Chronic Pulmonary Aspergillosis in a Post-treated Tuberculosis Patient - Christian Yong, Bernard Jonathan; Gunarsa, Ralph Girson (Publikasi Indonesia, 2022)
Chronic Pulmonary Aspergillosis (CPA) is a progressive respiratory syndrome of severe fungal infection typically found in immunocompetent or slightly immunocompromised patients with an underlying pulmonary disease. The underlying pulmonary disease typically includes active or post-tuberculosis, chronic obstructive pulmonary disease, or a history of surgery for lung cancer, for which tuberculosis remains the most common underlying condition. A 60 years old woman came with worsening dyspnea for the last 1 week, with hemoptysis and weight loss for the last 3 months, she has a history of pulmonary tuberculosis for 39 years, which was fully treated and she had completed the treatment regimen. A computed tomography (CT) scan was conducted, which showed solid fibroxanthoma with an air bronchogram in the upper left lung area. Transthoracic lung biopsy showed hyphae and fungal spores of Aspergillosis, which was supported by a positive Galactomannan test. Eventually, she was diagnosed with pulmonary aspergillosis and was advised to undergo surgical treatment with left pneumonectomy, but the patient refused surgical treatment. Chronic pulmonary aspergillosis is a progressive respiratory condition of severe fungal infection and is mostly found in post-tuberculosis patients. The symptoms may be similar to other chronic pulmonary diseases, making the diagnosis difficult. There are several reports that said pulmonary aspergillosis was misdiagnosed and only diagnosed only on autopsy. The mortality rate of this condition is quite high, and it typically worsens the quality of life.